Ecological correlates of mammal β‐diversity in Amazonian land‐bridge islands: from small‐ to large‐bodied species. Issue 8 (1st May 2018) - Palmeirim, Ana Filipa; Benchimol, Maíra; Morante‐Filho, José Carlos; Vieira, Marcus Vinícius; Peres, Carlos A.
Abstract: Aim: Mega hydroelectric dams have become one of the main drivers of biodiversity loss in the lowland tropics. In these reservoirs, vertebrate studies have focused on local (α) diversity measures, whereas between‐site (β) diversity remains poorly assessed despite its pivotal importance in understanding how species diversity is structured and maintained. Here, we unravel the patterns and ecological correlates of mammal β‐diversity, including both small (SM) and midsized to large mammal species (LM) across 23 islands and two continuous forest sites within a mega hydroelectric reservoir. Location: Balbina Hydroelectric Dam, Central Brazilian Amazonia. Methods: Small mammals were sampled using live and pitfall traps (48, 350 trap‐nights), and larger mammals using camera traps (8, 160 trap‐nights). β‐diversity was examined for each group using multiplicative diversity decomposition of Hill numbers, which considers the importance of rare, common and dominant species, and tested to what extent those were related to a set of environmental characteristics measured at different spatial scales. Results: β‐diversity for both mammal groups was higher when considering species presence–absence. When considering species abundance, β‐diversity was significantly higher for SM than for LM assemblages. Habitat variables, such as differences in tree species richness and percentage of old‐growth trees, were strong correlates of β‐diversity for both SMs and LMs. Conversely, β‐diversity was weakly related to patch and landscape characteristics, except for LMs, for which β‐diversity was correlated with differences in island sizes. Main conclusions: The lower β‐diversity of LMs between smaller islands suggests subtractive homogenization of this group. Although island size plays a major role in structuring mammal α‐diversity in several land‐bridge islands, local vegetation characteristics were additional key factors determining β‐diversity for both mammal groups. Maintaining the integrity of vegetation characteristics and preventing the formation of a large set of small islands within reservoirs should be considered in long‐term management plans in both existing and planned hydropower development in lowland tropical forests.